Perbedaan Hasil Belajar Biologi Antara Pembelajaran Berbasis Masalah Dengan Pembelajaran Berbasis Proyek Pada Siswa Kelas VII SMP Muhammadiyah 2 Surakarta Tahun Ajaran 2014/2015 - Octaviani, Steviana Ayu; , Dra. Aminah Asngad, M.Si (2015)
This research is an experimental research study that aims to improve student learning outcomes of class VII SMP Muhammadiyah 2 Surakarta. Classes are used in this study were randomly selected three classes (random) by using different learning. Data collection techniques in this study using the method of documentation and test methods. Analysis of data using statistical test One-Way ANOVA by SPSS 15.0 for windows. Results of the average value posttest using PBL students for (75,61±5,27) higher than using PJBL for (71,50±6,05) and the conventional method of (68,16±7,33). Hypothesis test results that look the value of F (15,293) is greater than the Ftable (3,101). Ftable value is obtained from the value of the significant level of 5% (df =2,87) that is equal to 0.05, then H0 is rejected means that there are significant differences between the three applied learning that PBL, PJBL, conventional. Further tests Anova result PBL learning and PJBL for 0,003<0,05 then H0 is rejected so there is a difference between the two. Comparison of PBL learning to control that 0,000<0,05 then, H0 is rejected so there is a difference. Conclusions that can be drawn from this research that there is a difference between PBL, PJBL and control with PBL better than PJBL and Control in the learning is done in class VII SMP Muhammadiyah 2 Surakarta 2014/2015 school year.